Growth and investigation of epitaxial GaBiAs layers / Epitaksinių GaBiAs sluoksnių auginimas ir savybių tyrimas - Andrius Ruseckas; Renata Butkutė; Klemensas Bertulis; Leonas Dapkus; Vaidas Pačebutas (Mokslas: Lietuvos Ateitis, 2011)
In this work the influence of technological parameters – Tp substrate temperature and Bi flux – on structural, electrical and optical properties of GaBiAs layers was investigated. Thin Ga-BiAs layers have been grown by molecular beam epitaxy tech-nology on monocrystalline GaAs substrates. The surface mor-phology of GaBiAs layers and formation of Bi droplets were examined using atomic force microscopy. The lattice parameters of GaBiAs and Bi concentration have been evaluated from high resolution X-ray diffraction ∆(2Θ)spektra. Optical measurements showed the reduction of energy band gap from 1.15 to 0.86 eV for GaBiAs layers with 4.4 and 11.3% of Bi concentration. From the Hall effect measurements using Van der Pauw geometry the highest carrier concentration 3.2∙1015 was measured for GaBiAs layers containing 11.3% of Bi.